Nutrient enrichment in wadeable urban streams in the Piedmont Ecoregion of the Southeastern United States. Issue 11 (November 2018) - Journey, Celeste A.; Van Metre, Peter C.; Waite, Ian R.; Clark, Jimmy M.; Button, Daniel T.; Nakagaki, Naomi; Qi, Sharon L.; Munn, Mark D.; Bradley, Paul M.
Abstract: The U.S. Geological Survey (USGS) Southeastern Stream Quality Assessment (SESQA) collected weekly samples for nitrogen and phosphorus in 76 wadeable streams in the urbanized Piedmont Ecoregion of the Southeastern United States, during April–June 2014. Total nitrogen (TN) concentrations in excess of U.S. Environmental Protection Agency (EPA) guidelines and statistically greater than at reference locations indicated nitrogen-nutrient enrichment in streams draining poultry confined animal feeding operations (CAFO) or urban centers. Nitrate plus nitrite (NO3 + NO2 ) dominated TN species in urban/CAFO-influenced streams. Streams that drained poultry CAFO and Washington DC had statistically higher NO3 + NO2 concentrations than streams draining Atlanta, Charlotte, Greenville, or Raleigh. In contrast, total phosphorus (TP) concentrations in Atlanta and Washington DC streams statistically were comparable to and lower than, respectively, reference stream concentrations. Over 50% of TP concentrations in Greenville, Charlotte, Raleigh and CAFO-influenced streams exceeded the EPA guideline and reference-location mean concentrations, indicating phosphorus-nutrient enrichment. Urban land use, permitted point sources, and soil infiltration metrics best predicted TN exceedances. Elevated TN and NO3 + NO2 concentrations in urban streams during low flow were consistent with reduced in-stream dilution of point-source or groundwater contributions. Urban land use, permitted point sources, and surface runoff metrics best predicted TP exceedances. Elevated TP in CAFO and urban streams during high flow were consistent with non-point sources and particulate transport.